2019
DOI: 10.3389/fcimb.2019.00410
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipidomics Analysis of Classical Swine Fever Virus Infection in Piglets and Emerging Role of Free Fatty Acids in Virus Replication in vitro

Abstract: Lipids metabolism plays a significant role in cellular responses to virus pathogens. However, the impact of lipids metabolism in CSFV infection is not yet confirmed. In the present study, for the fist time, we performed serum lipidomics analysis of piglets infected with CSFV based on ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS), and identified 167 differentially expressed lipid metabolites. Interestingly, free fatty acids (FFAs) accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…A decrease in [albumin] of ≥19% can significantly cause the release of bound Trp [ 28 ]. Serum [NEFA] has not been measured in COVID-19 patients, but is known to be elevated in infections with other viral classes, e.g., the flavivirus Dengue [ 42 ], the lentivirus HIV [ 43 ] and the asfivirus, the swine (fever) influenza [ 44 ]. Albumin depletion coupled with NEFA elevation provide the maximum effect on Trp binding and the resultant increase in free Trp availability can enhance the production of Kyn through IDO/TDO and thus provide the substrate for proinflammatory KP metabolite formation [ 26 ].…”
Section: What Needs To Be Measured In Covid-19 Patients?mentioning
confidence: 99%
“…A decrease in [albumin] of ≥19% can significantly cause the release of bound Trp [ 28 ]. Serum [NEFA] has not been measured in COVID-19 patients, but is known to be elevated in infections with other viral classes, e.g., the flavivirus Dengue [ 42 ], the lentivirus HIV [ 43 ] and the asfivirus, the swine (fever) influenza [ 44 ]. Albumin depletion coupled with NEFA elevation provide the maximum effect on Trp binding and the resultant increase in free Trp availability can enhance the production of Kyn through IDO/TDO and thus provide the substrate for proinflammatory KP metabolite formation [ 26 ].…”
Section: What Needs To Be Measured In Covid-19 Patients?mentioning
confidence: 99%
“…It has been shown that infection by some single-stranded RNA(ssRNA) viruses can alter the lipid metabolism and other biological processes of the host cells to facilitate the completion of the virus life cycle ( Sanchez and Lagunoff, 2015 ). Free fatty acids (FFAs), which can be used directly by the body for energy metabolism have been shown to be associated with the life cycle of various RNA viruses, including influenza A virus (IAV) ( Limsuwat et al, 2020 ), classical swine fever virus(CSFV) ( Ma et al, 2019 ), Middle East respiratory syndrome coronavirus (MERS-CoV) ( Yan et al, 2019a ), hepatitis C virus (HCV) ( Hofmann et al, 2018 ), zika virus (ZIKV) ( Queiroz et al, 2019 ) and ebola virus ( Kyle et al, 2019 ). Furthermore, some lipids are produced in the cells and others are imported from extracellular environment ( Limsuwat et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipids have also been shown to play important roles in the replication of coxsackievirus B3 ( Wang et al, 2020 ). An increased level fatty acid biosynthesis coupled with accumulation of free fatty acids that are associated with virus replication has been observed in host cells following CSFV infection ( Ma et al, 2019 ). Phosphorylated 5′-adenosine monophosphate-activated protein kinase induced by the infection of porcine reproductive and respiratory syndrome virus can inactivate the fatty acid biosynthesis pathway, playing an antagonistic role in the virus replication ( Long et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…VDAC1 could interact with IBDV Ribonucleoprotein (RNPs) and facilitates IBDV replication by enhancing IBDV polymerase activity (Han et al, 2017). In our previous work, we have confirmed that CSFV infection was closely associated with mitochondrial function (Gou et al, 2017;Ma et al, 2019). CSFV infection could induce mitochondrial fission and mitophagy to inhibit host cell apoptosis for persistent infection (Gou et al, 2017).…”
Section: Discussionmentioning
confidence: 79%